QUALITY OF FISH PREPARATIONS SERVED IN CATERING ESTABLISHMENT OF BOMBAY - DAMLE, S P; GARG, D K; NAMBIAR, V NARAYANAN; VASU, N M (Fishery Technology, 2017)
The results of the study carried out on the quality of fish preparations served in catering establishments of Bombay revealed that there is no serious potential health hazard to the consumer. Pathogens like Salmonella and Clostridium per were found to be absent. Based on organoleptic, biochemical and bacteriological parameters the quality of fish curry was better than that of fish fry. Overall quality of smaples from grade I establishments was better in comparison with grade II and III. However, a few samples of poor quality were also observed in grade I. Extraneous matter like hair and dead housefly were observed in a few samples from grade III indicating poor handling practices. The importance of good hygiene and sanitary practices in catering establishments is discussed